Chemical composition of the needle and cone essential oils of \(Pinus fenzeliana\) (Pinaceae) from Vietnam - Tran , Huy Thai; Nguyen, Thi Hien; Trinh , Xuan Thanh; Nguyen , Quang Hung; Paoli, Mathieu; Bighelli, Ange; Casanova, Joseph (Academia Journal of Biology, 2023)
The needle and cone essential oils of Pinus fenzeliana Hand-Mazz. (Pinus kwangtungensis Chun & Tsiang) collected in Hang Kia-Pa Co Nature Reserve, Hoa Binh province were obtained by hydrodistillation and analyzed by a combination of GC-FID, GC-MS and NMR (Gas Chromatography/Gas Chromatography-Mass Spectrometry/Nuclear Magnetic Resonance (NMR) analysis). The oil yields were 0.2% and 0.37% respectively (v/w on dry weight basis). Twenty-seven compounds were detected in both needle and cone oils, accounting for 98.0% and 98.2% of the whole composition, respectively. The main components identified in the needle oil were α-pinene (20.7%), β-pinene (11.3%), d-3-carene (32.2%), limonene (8.0%) and E-β-caryophyllene (7.1%). The cone oil contained mainly α-pinene (19.3%), β-pinene (45.4%), d-3-carene (3.5%), limonene (12.7%) and E-β-caryophyllene (3.4%). This is the first report on the chemical composition of the cone essential oil of P. fenzeliana from Vietnam.